ВИМІРЮВАННЯ ЕЛЕКТРОЕНЕРГІЇ В УМОВАХ НЕСИМЕТРІЇ СТРУМІВ ЗА ЧАСТКОВОЇ ВІДМОВИ СИСТЕМИ ОБЛІКУ - Говоров, П.П.; Момот, В.В. (Інститут електродинаміки НАН України, Київ, 2016)
The process of measurement of electric energy electronic meters for partial refusal of functioning of the electricity metering system have been research. The formulas for definition of values of correction coefficients that allow to compensate the measurement error of electricity, caused by a partial refusal of functioning in conditions of unbalance currents, have been received. Have been defined correction coefficients by different types of refusal and taking into account current unbalance. References 4, table 1, figures 3.